1995
DOI: 10.1002/eqe.4290240208
|View full text |Cite
|
Sign up to set email alerts
|

Passive seismic control of cable‐stayed bridges with damped resonant appendages

Abstract: SUMMARYA study is conducted to investigate the effectiveness of attaching to cable-stayed bridges resonant appendages with a relatively small mass and a high damping ratio as a means to reduce their response to earthquake excitations. The study is based on a previously developed formulation that shows that the use of these appendages may increase the inherent damping of building structures and, as a result, may reduce their response to seismic disturbances. It includes numerical and experimental tests that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…For example, Xu and Kwok [18] found that the e$cacy of PTMD was not as good as expected based on a wind tunnel test of a tall building subjected to along, cross and torque wind excitations. Villaverde [19] investigated the PTMD e!ectiveness through three di!erent structures subjected to nine actual earthquake records. He found that PTMD had good performance in some cases, but some had little or even no e!ect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xu and Kwok [18] found that the e$cacy of PTMD was not as good as expected based on a wind tunnel test of a tall building subjected to along, cross and torque wind excitations. Villaverde [19] investigated the PTMD e!ectiveness through three di!erent structures subjected to nine actual earthquake records. He found that PTMD had good performance in some cases, but some had little or even no e!ect.…”
Section: Introductionmentioning
confidence: 99%
“…Without scrutinizing the details of these studies, it is not straightforward to identify the precise reason (or reasons) for these con icting conclusions. However, Villaverde and his associate [10][11][12] o er, perhaps, the most convincing argument for these di erent ÿndings. They observe that the primary reason for ine ectiveness of the dampers is the use of the classical solutions that are not necessarily optimal for the particular situation under study.…”
Section: Introductionmentioning
confidence: 89%
“…However, lack of knowledge exists in the control of very flexible bridge structures which generally exhibit a complex dynamic behavior during wind and earthquakes. In deed, structural control of flexible long-span bridge structures such as cablestayed bridges has recently attracted so much interest among researchers around the world (e.g., Achkire 1997; Ali and Abdel-Ghaffar 1994; Betti and Testa 1995;Preumont et al 1999;Ni et al 2001b;Shoureshi and Bell 1996;Villaverde and Martin 1995;Wesolowsky and Wilson 2003;Wilde and Fujino 1998) that a benchmark structural control problem (Dyke et al 2000) has been proposed for cable-stayed bridge studies by a task group of the American Society of Civil Engineers (ASCE). The benchmark problem, which is a 3-d linear evaluation model, is based on a cable-stayed bridge located in Missouri, USA.…”
Section: Technologies For Long-span Cable-supported Bridges 321mentioning
confidence: 99%